Comparative analysis of the Spanish and United Kingdom sport-political models - Puga-González, M. E.; Pappous, A.; Gómez-Píriz, P. T.; González-Ruíz, J.; Cabello-Manrique, D. (Journal of Human Sport & Exercise, 2023)
This research conducts a comparative study between the sports models of the United Kingdom (UK) and Spain, emphasizing the complexity of these systems and the need for a multidimensional analysis. The objective of analysing the most important characteristics and differences between the Spanish sports model and structure and the UK sports model, the leading exponent due to its efficiency in the development of sports practice and in obtaining international sports results, to determine possible improvements. To carry out this study, a comparative analysis of the sports models of both countries has been made from a political-sports perspective, and the study of the administrative-organizational structure of sport and the legal regulations that support it, through a mixed design for the analysis of different qualitative dimensions. The most significant conclusions are that in the United Kingdom, a successful transformation has been achieved with a focus on efficiency, public investment, and private partnerships, while in Spain, sporting results have been maintained without a clear strategy, suggesting the need for a re-evaluation of its model. Moreover, the stronger associative culture and a higher number of qualified professionals in the United Kingdom are significant advantages. In conclusion, the United Kingdom's sports model is considered more developed and efficient, highlighting the importance of comprehensive planning and collaboration between public and private entities as key factors for sporting success.